Analisis Rasio Likuiditas dan Rentabilitas Untuk Mengukur Kinerja Keuangan PT Adhi Karya, Tbk - Ugeng Budi Haryoko; Fauziah Septiani; Novelina Novelina (Indonesian Journal of Economics Application (IJEA), 2020)
The company's financial performance at PT Adhi Karya Tbk. by using financial ratio analysis during the period 2011-2017. The ratio used is the Liquidity Ratio and the rentability ratio. The research method used is data analysis techniques using the ratio analysis technique that is describing a relationship between a certain amount and the other number. Ratio analysis used is the analysis of the ratio of liquidity and profitability where the liquidity ratio aims to determine the company's ability to meet its short-term obligations. The profitability ratio aims to measure the company's ability to seek profits. Measuring of financial performance by using liquidity and profitability ratios Rentability Ratio at PT Adhi Karya Tbk. Showing financial performance that is less efficient in terms of the average value of the Return on Equity ratio is still below the industry standard average. The Return on Investment ratio is inefficient because the value of the company's net income tends to decrease and is below the industry standard average. Analysis of the Liquidity ratio seen from the Current Ratio is still below the industry average so that financial performance is illiquid. Meanwhile, Cash Ratio performance is below the industry standard (illiquid).